2011
DOI: 10.1007/s00508-010-1527-6
|View full text |Cite
|
Sign up to set email alerts
|

Dominance of CTX-M group 1 beta-lactamase enzymes in ESBL producing E. coli from outpatient urines in neighboring regions of Austria and Italy

Abstract: The importance of extended spectrum β-lactamases (ESBL) is increasing worldwide. ESBLs of the CTX-M type are on the rise in Europe, not only in the hospital environment but also in outpatients. Therefore we performed a comparative pilot study including ESBL producing Escherichia coli isolated from outpatients suffering from urinary tract infections, 28 from Innsbruck, Austria, and 34 from Bolzano, Italy. Using established PCR methods we detected in nearly 90% of ESBL producing E. coli isolates CTX-M group 1 en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Although the rate of CTX-M production varied between hospitals (1.2 to 49.5% of ESBL producers), all these isolates belonged to CTX-M group 1 with CTX-M-15 and CTX-M-1 being the most prevalent variants (60% and 35%, respectively) and CTX-M-32 carried only by a minority (5%). In 2011, the dominance of CTX-M group 1 ESBL-producing E. coli causing urinary tract infections among outpatients was reported (Huemer et al, 2011). More recently, an outbreak of colonization by ESBL producing E. coli sequence type 11 was identified in a neonatal intensive care unit.…”
Section: Predominant Esbls Circulating In European Countries On the Mmentioning
confidence: 99%
“…Although the rate of CTX-M production varied between hospitals (1.2 to 49.5% of ESBL producers), all these isolates belonged to CTX-M group 1 with CTX-M-15 and CTX-M-1 being the most prevalent variants (60% and 35%, respectively) and CTX-M-32 carried only by a minority (5%). In 2011, the dominance of CTX-M group 1 ESBL-producing E. coli causing urinary tract infections among outpatients was reported (Huemer et al, 2011). More recently, an outbreak of colonization by ESBL producing E. coli sequence type 11 was identified in a neonatal intensive care unit.…”
Section: Predominant Esbls Circulating In European Countries On the Mmentioning
confidence: 99%
“…However, communityacquired ESBL producingeE coli, especially of CTX-M-type ESBL, has now become a growing problem worldwide and has changed the epidemiology of infections related to antibiotic-resistant bacteria. 2,3,4,5 Similarly, plasmidmediated ACBL-producing bacteria also serve as communitybased reservoirs for 3GC-R strains. 3,6 Effective treatments for infections caused by ESBL-producing E coli or K pneumoniae are limited to only a few antibiotics, including carbapenems and noneb-lactam antibiotics.…”
Section: Introductionmentioning
confidence: 99%
“…11 ESBL-producing E. coli strains isolated from Austria and Italy showed that they expressed CTX-M group I enzymes predominantly. 12 Molecular characterization of ESBLs in 440 E. coli isolates from 10 centers between 2011 and 2012 was examined. Molecular analyses of particular ESBL types on a national level performed in district hospitals have contributed to a better understanding of the epidemiology of the strains producing these enzymes at local, national and international level.…”
Section: Introductionmentioning
confidence: 99%